PROTOTYPE GENERATOR MAGNET PERMANEN MENGGUNAKAN KUMPARAN STATOR GANDA - Hartono, Hartono; Sugito, Sugito; Wihantoro, Wihantoro (BERKALA FISIKA, 2014)
A permanent magnet generator has had been built using double stator coil.Â Such coil was used to increase the electrical energy produced. This is apparently a type of single phase generator equipped by four permanent magnets of 2.5 cm in diameter and length each. Each of the four magnets has 4000 Gauss magnetic strength. The coil itself made from email wire of 0.12 mm in diameter and has 1200 turns. The performance of generator was tested on a rotor that turn by 300, 600, 900 and 1200 rpms each. The testing was performed on a condition with and without any load resistance. Testing result without load resistance showed the increase average output voltage about 83.95%, where the generator with load resistance has increase average output voltage about 62.65%.Keywords: generator, permanent magnet, double stator, increase the electrical energy